Isomerização de n-hexano sobre Pt-NiHUSY empregando zeolita com alto teor de Al - Barsi, Fabrício Ventura (Universidade Federal de São Carlos, 2005)
The isomerization reactions of linear alkanes are very important to petrochemical industries due to the isomer products in reaction possess high octane number. The majority of the literature articles involves the job of bifunctional catalysts, in the other words, catalysts containing acid sites and metallic sites. In this work, monometallic (Ni or Pt) and bimetallic (Pt-Ni) bifunctional catalysts were prepared using the USY zeolite (acid sites). The method utilized to disperse the metals in the zeolite was the competitive ion exchange, using its amin complexes [Ni(NH3)6]Cl2 and [Pt(NH3)4]Cl2 as precursors. Three series of catalysts were prepared containg a constant atomic metal: 130, 180, 230 and 280.10-6 atg Me.gcat -1. The catalysts had been characterized by reduction temperature programmed (TPR) and submitted to the catalytic evaluation using the n-hexane isomerization reaction at 250 ºC, 1 atm and a ratio H2/C6 = 9. In the TPR results, a larger reducibility of cations Ni2+ was verified when in presence of Pt, evidenced for the displacement of the peak of reduction to lower temperatures in the monometallic catalysts front to the bimetallic. In the isomerization of n-hexane, the bimetallic catalysts presented a higher activity and selectivity to isomers compared to the monometallic ones, and the stability increased with the content of Pt in the solid. Comparing the monometallic catalysts of Ni and Pt, it was observed that monometallic catalysts of Pt, presents higher activity and lower eactivation. Evaluating the activity in function of the content of Pt, it was observed a maximum for lower content of Pt (about 50%). Above of this content, an addition of Pt leads to the reduction of the initial catalytic activity.
Keywords: Catalise; Isomerização; Zeolita Y; Catalisadores bimetálicos; ENGENHARIAS::ENGENHARIA QUIMICA